The Santa Clause [videorecording (DVD)] - Pasquin, John; Allen, Tim, 1953-; Reinhold, Judge, 1957-; Crewson, Wendy; Boyle, Peter, 1935-2006; Lloyd, Eric; Krumholtz, David, 1978- (Walt Disney Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2002)
Scott is distressed to learn that his ex-wife and her husband have informed his son, Charlie, that there is no Santa Claus. While a sullen Charlie visits his dad on Christmas Eve, a noise on the roof brings them outside. It turns out that there is a Santa after all, and Scott has just accidentally killed him. Because of "the Santa clause," Scott inherits the job of Santa. As the next year passes, Scott rapidly gains weight, grows a white beard and meets the elf Bernard. Charlie's stepdad becomes concerned about Scott's and forces him to undergo a psychiatric evaluation.